Deradikalisasi Agama melalui Pendidikan Multikultural (Studi Kasus di Fakultas Tarbiyah dan Keguruan UIN Sunan Ampel Surabaya) - Syafii Syafii; Sutikno Sutikno; Fathur Rohman (MODELING: Jurnal Program Studi PGMI, 2022)
Violence in the name of religion can occur anywhere and anytime, both involving Muslims and non-Muslims. That is, religious radicalism is actually a phenomenon that commonly appears in any religion. Higher education institutions are very likely to become clusters of spreading seeds of radicalism. Not a few students become special targets of recruitment of terrorist and radical groups. Therefore, a religious deradicalization program is needed through multicultural education. Deradicalization is a solution to straighten out radical understanding in religion in order to create a society that is tolerant, inclusive, humanist, plural and democratic. Multicultural education is a tool to realize deradicalization in religion. Deradicalization of religion through multicultural education at the Faculty of Tarbiyah and UIN Sunan Ampel Surabaya Teacher Training is implemented with curriculum development model, selection of lecture materials and literature, lecture methods, (workshop) activities and cooperation. Factors supporting the deradicalization of religion through multicultural education at the Faculty of Tarbiyah and UIN Sunan Ampel Surabaya Teacher Training include the coordinated of all lecturers and employees by applicable rules, the exemplary lecturer with a professorship and become a national figure, gaining support from the Ministry of Religious Affairs. While the inhibiting factors include differences in the flow of religious organizations, differences in student intelligence levels, advances in information technology.